84.5k views
3 votes
Select all the equations that have no solution and state your reasoning as of "why" they do not have a solution. +6=5+ x+6=5+x −2(−3)=-2+6 −2(x−3)=-2x+6 4−4=3+2 4−4x=3x+2 4(+1)=3(+2) 4(x+1)=3(x+2) 5−3=-3+4 5−3x=-3x+4

User Boss Nass
by
4.5k points

1 Answer

7 votes

Equations:


x+6=5+x


-2(x-3)=-2x+6


4-4x=3x+2


4(x+1)=3(x+2)


5-3x=-3x+4

Answer:


x+6=5+x


5-3x=-3x+4

Explanation:

Given


x+6=5+x


-2(x-3)=-2x+6


4-4x=3x+2


4(x+1)=3(x+2)


5-3x=-3x+4

Required:

Which have no solution


x+6=5+x

Subtract x from both sides


x -x+6 = 5 + x - x


6 = 5


x+6=5+x has no solution because
6 \\e 5


-2(x-3)=-2x+6

Open bracket


-2x + 6 = -2x + 6

Both sides are equal.

Hence, there is an
Infinite\ Number of Solutions


4-4x=3x+2

Collect like terms


-3x - 4x = 2 - 4


-7x = -2

Solve for x


x = (-2)/(-7)


x = (2)/(7) --- This has a solution


4(x+1)=3(x+2)

Open brackets


4x + 4 = 3x + 6

Collect like terms


4x-3x = 6 - 4


x = 2 --- This has a solution


5-3x=-3x+4

Add 3x to both sides


5 - 3x + 3x = -3x + 3x + 4


5 = 4


5-3x=-3x+4 has no solution because
5 \\e 4

User Max Tepkeev
by
4.1k points